2016
DOI: 10.1038/srep28235
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deposition and management practices increase soil microbial biomass carbon but decrease diversity in Moso bamboo plantations

Abstract: Because microbial communities play a key role in carbon (C) and nitrogen (N) cycling, changes in the soil microbial community may directly affect ecosystem functioning. However, the effects of N deposition and management practices on soil microbes are still poorly understood. We studied the effects of these two factors on soil microbial biomass carbon (MBC) and community composition in Moso bamboo plantations using high-throughput sequencing of the 16S rRNA gene. Plantations under conventional (CM) or intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 63 publications
4
48
0
Order By: Relevance
“…Our previous study [21] at this site demonstrated that differences in microbial community structure were primarily due to a combination of N deposition and management practices (57.73%), with management practices alone accounting for 36.26% of the variation and N addition accounting for 21.47%, indicating that the combination of two factors has a stronger impact on DOM than each factor singly, which also supported our present result. In summer, the positive effects of high temperature partially offset the negative effects of N deposition and IM alone on DOC and DON, thus contributing to the low combination of these two factors (Table 2).…”
Section: Combined Influence Of N Deposition and Management Practices supporting
confidence: 91%
See 4 more Smart Citations
“…Our previous study [21] at this site demonstrated that differences in microbial community structure were primarily due to a combination of N deposition and management practices (57.73%), with management practices alone accounting for 36.26% of the variation and N addition accounting for 21.47%, indicating that the combination of two factors has a stronger impact on DOM than each factor singly, which also supported our present result. In summer, the positive effects of high temperature partially offset the negative effects of N deposition and IM alone on DOC and DON, thus contributing to the low combination of these two factors (Table 2).…”
Section: Combined Influence Of N Deposition and Management Practices supporting
confidence: 91%
“…Yang et al [31] proved that the growth of plant roots and soil microorganisms (represented by MBC) was enhanced by fertilization, increasing the amount of organic compounds (i.e., DOM) released by plant roots and soil microorganisms. Our previous study on this site showed that IM significantly increased soil MBC [21], indicating an increase in DOC consumption, which might greatly contribute to lower DOC concentrations in the IM plots than in the CM plots. Changed nutrient dynamics caused by management practices can also affect DOM concentrations between the native forests and plantations [27].…”
Section: Effects Of Management Practices On Soil Doc and Donmentioning
confidence: 78%
See 3 more Smart Citations